The use of a modification of the Hurwicz’s decision rule in multicriteria decision making under complete uncertainty - Gaspars-Wieloch, Helena (Business, Management and Economics Engineering, 2014)
The paper concerns multicriteria decision making under uncertainty with scenario planning. This topic is explored by many researchers because almost all real-world decision problems have multiple conflicting criteria and a deterministic criteria evaluation is often impossible (e.g. mergers and acquisitions, new product development). We propose two procedures for uncertain multi-objective optimization (for dependent and independent criteria matrices) which are based on the SAPO method – a modification of the Hurwicz’s rule for one-criterion problems, recently presented in another paper. The new approaches take into account the decision maker’s preference structure and attitude towards risk. It considers the frequency and the level of extreme evaluations and generates logic rankings for symmetric and asymmetric distributions. The application of the suggested tool is illustrated with an example of marketing strategies selection.